Studi Status Hara Ca dan Mg Sawah Tadah Hujan Desa Malek Kecamatan Paloh Kabupaten Sambas - gunawan, denny; Ir. Rita Hayati, M.Si, Ir. Rita Hayati, M.Si; Ir. Ismahan Umran, M.Si, Ir. Ismahan Umran, M.Si (Fakultas Pertanian Universitas Tanjungpura, 2016)
This study aims to determine the nutrient status of calcium and magnesium for rice crops in rainfed rice cultivation Malek village Paloh District of Sambas district. Study nutrient status Ca and Mg conducted extensive research sites 8 ha, followed by soil analysis in the laboratory. The method used in this research is to use the survey method. The experiment was conducted in November 2015 until January of 2016. The study variables: (1) calcium exchanged, (2) magnesium exchanged, (3) the pH of the soil, (4) test pyrite. Based on the analysis of chemical properties and soil fertility in the laboratory that the calcium levels between 2.26 to 3.36 with the criteria of low levels of magnesium values